2011
DOI: 10.7317/pk.2011.35.3.244
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characteristics of Poly(phenylene ether)s in Various Reaction Conditions

Abstract: PPE는 poly(phenylne oxide), poly(phenylene ether), 및 poly (arylene ether) 등으로 불리는 엔지니어링 플라스틱의 일종으로서 PPE의 연구는 1915년에 최초로 시작되었으나 분자량과 수율이 낮 아 공업적으로 관심을 끌지 못했다. 그후 1957년에 미국 General Electric사의 Hay가 Scheme 1에 나타낸 바와 같이 2,6-dimethylphenol(DMP)의 Cu/amine complex를 촉매로 사용한 산화커플링 중합으로 고분자량의 PPE 합성에 성공함으로써 새로운 엔지니어링 플라스틱으로 발돋음하게 되었다. 1-4 PPE는 기계적, 전기적 특성이 매우 뛰어나고 내열성, 내화학성 및 치수 안정성 등 물성이 우수하며 5 유리전이온도(T g )가 205 ℃로 높 고 -20 ℃의 낮은 온도에서도 우수한 충격 강도를 나타낸다. PPE의 융점(T m )은 267 ℃로 보고되고 있으나 결정화도가 5∼10%에 불과 하기 때문에 통상 무정형 고분자로 구분되고… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Table 12 presents the physical property data that required input for injection molding analysis under the categories of mechanical properties, fluid properties, and thermal properties, which were the criteria for sample selection. In the aforementioned tensile strength test, both elastic modulus and Poisson's rate were measured, and the shear modulus can be obtained using Equation (1). Table 13 shows the results of experiments on tensile strength, elastic modulus, and shear modulus for each sample.…”
Section: Physical Property Data Required For Injection Molding Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Table 12 presents the physical property data that required input for injection molding analysis under the categories of mechanical properties, fluid properties, and thermal properties, which were the criteria for sample selection. In the aforementioned tensile strength test, both elastic modulus and Poisson's rate were measured, and the shear modulus can be obtained using Equation (1). Table 13 shows the results of experiments on tensile strength, elastic modulus, and shear modulus for each sample.…”
Section: Physical Property Data Required For Injection Molding Analysismentioning
confidence: 99%
“…Additionally, PPOs are not affected by most acids, alkalis, or organic solvents. Despite these excellent properties, PPOs have disadvantages in that they are not suitable for processing due to their high molding temperatures and poor fluidity when being molded into products [1].…”
Section: Introductionmentioning
confidence: 99%
“…1,2017 In recent years, polymer/clay nanocomposites have attracted great attention in both academic and industrial researches, due to their synergistic advanced properties at realtively low nanoclay loadings (up to 5 wt%). [7][8][9][10][11][12] The typical enhanced properties include tensile strength, heat deflection temperature, barrier properties, and so on. [13][14][15] Because of these good properties and low price, industrial applications of nanoclay also found great attraction nowadays.…”
Section: Introductionmentioning
confidence: 99%
“…The use of GPC to determine molecular weights of fullerene-containing compounds has been performed previously using polystyrene standards and RI detection [26,27,[41][42][43][44][45]. In our case, the addition of PDA detection allowed for peak identification of the compounds of interest based upon their UV-Visible absorption spectra (since the chromophore absorption spectrum stays relatively consistent before and after polymerization, vide infra) and the corresponding RI peak used for molecular weight determination.…”
Section: Gpc Characterizationmentioning
confidence: 99%